Academic Language and Learning (ALL) in Australia: An endangered or evolving species? - Malkin, Carolyn; Chanock, Kate (Journal of Academic Language and Learning, 2018)
This paper reflects on our findings from a survey designed to explore a shift in the roles and responsibilities of Academic Language and Learning (ALL) practitioners in the 21st century and to consider what this shift might mean for our professional future. With the trend towards increasing collaborations among ALL, AD, educational designers and discipline lecturers, many of us hope this may mitigate the marginalisation commonly expressed by ALL practitioners, although a merging of roles may also risk devaluing of the particular knowledge, skills, values and purposes that have shaped ALL work. Our research aimed to discover how our colleagues are situated in this shift, and its implications for their sense of purpose, possibility, and satisfaction in their work. Closed questions obtained information on the educational and cultural experiences that have brought colleagues into the field, and how their work is positioned currently in their institutions. Open questions elicited their thoughts on how their education and experience have shaped their work and the field more broadly, and how current trends are likely to impact their commitment and satisfaction in ALL work.